(3GJMGa Phj GdGSJMbGb HHYV eQGO GdeQGOj hRhGFO CHj ESMGbs - (3eMeO Hf CMeO Hf eMeO Hf eMeO Hf Ydj Hf ZGRj GdYKeGfj GdecfGSj , GHf ZGRj , CHh YHO Gddg,J (B919 (3g` s ((3CMeO Hf CHj HcQ GdSfaGQi GdeGdci s)
(3ChdgG (B:s
(3CeG HYO agPG GJNGa Phi GdGSJMbGb HHYV eQGO GdeQGOi hRhGFO CHj GSMGb hGddg GdeSJYGf ai aJM GdGSJZdGb hfXe GdTed hLejY GdGaJQGb s
(3BNQgG (B:s
(3gfG GfJgi eG bUOfG LeYg ai Md HYV eTcdGJ cdGe GdGeGe CHj Ydi GdeQGOi hJWQjRg HHYV eG SeY ef fcJ CHj GSMGb GdTGWHi s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B336 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B16 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B226s
Keywords: (3eJaQbGJs